Impacts of Bacteriostatic and Bactericidal Antibiotics on the Mitochondria of the Age-Related Macular Degeneration Cybrid Cell Lines - Nasim Salimiaghdam; Lata Singh; Mithalesh K. Singh; Marilyn Chwa; Shari R. Atilano; Zahra Mohtashami; Anthony B. Nesburn; Baruch D. Kuppermann; Stephanie Y. Lu; M. Cristina Kenney (Biomolecules, 2022)
We assessed the potential negative effects of bacteriostatic and bactericidal antibiotics on the AMD cybrid cell lines (K, U and J haplogroups). AMD cybrid cells were created and cultured in 96-well plates and treated with tetracycline (TETRA) and ciprofloxacin (CPFX) for 24 h. Reactive oxygen species (ROS) levels, mitochondrial membrane potential (ΔψM), cellular metabolism and ratio of apoptotic cells were measured using H2DCFDA, JC1, MTT and flow cytometry assays, respectively. Expression of genes of antioxidant enzymes, and pro-inflammatory and pro-apoptotic pathways were evaluated by quantitative real-time PCR (qRT-PCR). Higher ROS levels were found in U haplogroup cybrids when treated with CPFX 60 µg/mL concentrations, lower ΔψM of all haplogroups by CPFX 120 µg/mL, diminished cellular metabolism in all cybrids with CPFX 120 µg/mL, and higher ratio of dead cells in K and J cybrids. CPFX 120 µg/mL induced overexpression of IL-33, CASP-3 and CASP-9 in all cybrids, upregulation of TGF-β1 and SOD2 in U and J cybrids, respectively, along with decreased expression of IL-6 in J cybrids. TETRA 120 µg/mL induced decreased ROS levels in U and J cybrids, increased cellular metabolism of treated U cybrids, higher ratio of dead cells in K and J cybrids and declined ΔψM via all TETRA concentrations in all haplogroups. TETRA 120 µg/mL caused upregulation of IL-6 and CASP-3 genes in all cybrids, higher CASP-7 gene expression in K and U cybrids and downregulation of the SOD3 gene in K and U cybrids. Clinically relevant dosages of ciprofloxacin and tetracycline have potential adverse impacts on AMD cybrids possessing K, J and U mtDNA haplogroups in vitro.